EFFECTIVENESS OF TEACHING ELEMENTS OF COMMUNICATION TECHNIQUES IN THE PRIMARY PREPARATORY GROUP (World Bulletin of Physical Education and Sports Science, 2026)
This article examines the effectiveness of teaching elements of communication techniques in the primary preparatory group from a pedagogical perspective. At the present stage of educational development, special attention is being paid to the formation of children’s communicative competence before they enter formal schooling, since communication skills serve as an essential foundation for social adaptation, collaborative learning, and personal development. The study focuses on the pedagogical conditions, methods, and interactive approaches that support the development of basic communication techniques in young learners. Particular emphasis is placed on speech activity, listening culture, dialogic interaction, emotional responsiveness, and the ability to express thoughts clearly in age-appropriate situations. The article analyzes the role of play-based tasks, situational exercises, visual aids, and cooperative activities in improving children’s verbal and nonverbal communication. It is argued that the systematic teaching of communication elements in the primary preparatory group contributes to greater confidence, improved peer interaction, active participation in educational tasks, and readiness for school-based instruction. The findings support the view that purposeful pedagogical work in this area enhances both language development and broader social competence.
Keywords: Communication techniques, primary preparatory group, communicative competence, speech development, interactive methods, preschool education, dialogic speech, social adaptation, cooperative learning, school readiness